Different models of transition to adult care after pediatric kidney transplantation: A comparative study. (4th June 2013) - Pape, L.; Lämmermühle, J.; Oldhafer, M.; Blume, C.; Weiss, R.; Ahlenstiel, T.
Abstract: Transition from pediatric to adult care is a critical and difficult step for young people with transplants and for the multidisciplinary team involved. In our retrospective study, we investigated the clinical course in a two‐yr period of transition. Data from 66 teenagers were collected one yr before and after their transfer to three different adult care settings: (i) a specialized transition clinic, (ii) a general transplantation clinic, and (iii) a nephrologist. Patient survival rate was 100%. Three patients developed graft loss. GFR development was comparable in the three settings (ΔGFR 1.4 ± 8.7 vs. 3.1 ± 10.6 vs. 0.8 ± 4.4 mL/min/1.73 m 2, p = ns). Immunosuppressive therapy was stable in setting 1, whereas the number of changes increased in setting 2 and even more in setting 3. The percentage of patients with steroids increased from 36% to 38% and 52% in settings 1–3. Patient satisfaction was highest in setting 1 (100% vs. 64% and 78%, p < 0.05). Setting 1 was associated with fewer changes in therapy (13% vs. 91% and 45%, p < 0.05). The use of a specialized transition clinic is associated with fewer changes in medication and care and a higher level of patient satisfaction. This was not associated with a lower increase in GFR one yr after transition. Long‐term results are awaited.